Improving Access and Quality in the Indian Education System - Hill, Sam (OECD Economics Department Working Papers, 2011)
Education has been given high priority by India's central and state governments and continues to grow fast. School access has been expanded by investment in school infrastructure and recruitment of teachers. In higher education too, the number of providers continues to rise rapidly. A new law enshrining the rights of all children to free and compulsory education will further lift enrolment, bringing closer the government's goal of universal elementary education, which comprises eight years of schooling. Nevertheless, high drop-out rates and low attendance continues to be a challenge at lower levels and enrolment at higher levels remains modest by international standards. Private sector involvement is on the rise. While it helps expand education infrastructure, particularly in higher education, access has not always been assured and the availability of student loans for higher education needs to improve. Poor learning outcomes amongst school students and mediocre higher education provision call for more effective government regulation and funding arrangements. Expanding resources will help but they need to be deployed more effectively, while incentives and professional development systems for teachers need to be strengthened. In higher education the government has proposed reforms which have the potential to bring about much-needed improvements in regulatory effectiveness. Efforts should focus on reducing micro-regulation and improving institutional autonomy, in order to stimulate innovation and diversity. Increasing the number of institutions subjected to quality assessments will be important for lifting standards across the higher education system, while reform of recruitment and promotion mechanisms could help attract and retain talent in academia